Green Marketing Strategies as A Competitive Advantage in Small and Medium Enterprises: A Systematic Literature Review - Dariyanti; Ebrahim Mohammed (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This examine investigates green marketing strategies as a competitive advantage for small and medium enterprise (SMEs) of the 450 searched studies, 45 met the eligibility criteria for review by a systematic literature review of peer-reviewed articles, conference papers, and enterprise reports between 2020 and 2025 from the databases like Scopus, Web of Science. Amid growing sustainability demands, SMEs adopt green practices such as sustainable product improvement, eco-labeling, green deliver chain management, green marketing, and corporate social responsibility to enhance market positioning. These techniques improve emblem image, consumer loyalty, operational performance, and profitability. However, barriers like limited monetary resources, lack of understanding, and inadequate authorities assist impede adoption. The review reported that evaluate identifies a research gap in quantifying green marketing's direct effect on SMEs economic performance. Synthesizing present day expertise, this examine offers actionable insight for SMEs, policymakers, and researchers. It proposes a singular conceptual framework linking green marketing and marketing techniques to competitive benefit, supplying a basis for future empirical research in sustainable enterprise practices.